Influence of the ribs parallel to web on warping and load-bearing capacity of a steel I-beam - Wierzbicki, Krzysztof; Szumigała, Maciej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article analyses the method of enhancing a steel beam by adding additional steel members like ribs. They are rigidly connected with both flanges in a plane parallel to the web. That plates reduces warping during in-plane bending of steel beam under lateral-torsional bucking.
Keywords: steel beam; warping; lateral-torsional buckling; enhancing; ribs parallel; bending; belka stalowa; odkształcenia; wzmocnienia